Morphology and physical properties of ceramic hollow fibre membrane: effect of different bore fluid flow rates - Siti Salwa Alias,; Zawati Harun,; Ahmad Nazreen Ahmad Ismail,; Noor Hasliza Kamarudin, (Penerbit Universiti Kebangsaan Malaysia, 2019)
The study on ceramic hollow fibre membrane (CHFM) has been extensively explored. In this study, the CHFM was fabricated via extrusion combined with phase inversion and sintering method using silica, alumina with polyethersulfone binder and N-Methyl-2-pyrrolidone solvent at different bore fluid flow rates (10, 15 and 20 mL min-1) and sintered (1200°C). The CHFM extruded at a flow rate of 10 mL min-1 and sintered (BF10-B) showed the good porous cross-sectional hollow surface compared to the dense agglomerated surface of BF15-B and BF20-B. The highest Rq (82.1 μm) and Ra (67.8 μm) were obtained from BF10-B based on topography analysis which corresponded to the higher pore entrances of the membrane. The porosity decreased inversely proportional with the density as the bore fluid flow rate increased confirming that the suppression of un-solidified particles in the inner region cannot occur completely at a high bore fluid flow rate and produced dense membrane. The fabricated CHFM in this study has the broad potential to be applied as a membrane for water separation since it meets the minimum requirement of a commercial ceramic membrane.